Integrated Stratigraphy of the Cenozoic Andean Foreland Basin (Northern Argentina) - Galli, Claudia Inés (2017)
The stratigraphic and sedimentologic characteristics of Cenozoic deposits in north‐western Argentina represent important tectono‐sedimentary constraints on the evolution of the Andean foreland basin in this region. This nonmarine unit unconformably rests on the top of the postrift deposits of the middle Eocene Lumbrera Formation (Santa Bárbara Subgroup, Salta Group) or on older deposits. Eocene‐Pliocene paleoenvironmental changes were the direct result of changes in the tectonic setting and accommodation space. This study describes the results of an integrated analysis of the middle‐upper Eocene to Plio‐Pleistocene deposits filling the basins of the Cordillera Oriental. Fluvial deposits associated with different topographic slopes characterize the basins that formed in the Central Andes of north‐western Argentina due to Cenozoic tectonic convergence. The formation of these basins led to the development of continental sedimentary environments, including an ephemeral fluvial system with aeolian dune fields; a sandy braided fluvial system; a playa lake; a sinuous gravelly sandy fluvial system with lagoons; and lagoons and marshes. These basins, which were probably connected during the first stage of their development, are characterized by different subsidence histories, sedimentary paleoenvironmentalevolution patterns, topographic slopes, provenances, and paleocurrentdirections, resulting in different tectono‐sedimentary histories.